2009
DOI: 10.1016/j.jcrs.2008.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Collagen crosslinking with ultraviolet-A and hypoosmolar riboflavin solution in thin corneas

Abstract: Corneal collagen crosslinking (CXL) with riboflavin and ultraviolet-A light is a method for treating progressive keratectasia. The currently accepted treatment parameters induce collagen crosslinking in the anterior 250 to 350 mm of corneal stroma. To protect the endothelium, CXL inclusion criteria require a minimum corneal thickness of 400 mm after removal of the epithelium. In advanced keratoconus, however, progressive corneal thinning often leads to a remaining stromal thickness of less than 400 mm. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
239
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(254 citation statements)
references
References 19 publications
3
239
0
12
Order By: Relevance
“…C-CXL requires corneal pachymetry of at least 400 µm to protect the endothelial cells 25 . Its major drawbacks are related to time duration (1 hr) and the necessity to remove the epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-CXL requires corneal pachymetry of at least 400 µm to protect the endothelial cells 25 . Its major drawbacks are related to time duration (1 hr) and the necessity to remove the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that patients with thin corneas (minimal thickness of 350-400 µm) may benefit from the accelerated CXL. At this time, a hypo-osmolar riboflavin that leads to swelling of thin corneas before C-CXL is used since this protocol still requires corneal pachymetry of at least 400 µm to prevent endothelial damage 25 . Nonetheless, accelerated CXL may be preferentially used in the future as a faster and less penetrating treatment to stabilize keratoconus for thinner corneas.…”
Section: Discussionmentioning
confidence: 99%
“…27 Hypotonic riboflavin is now commonly used to increase corneal thickness before UVA exposure in thinner corneas. This technique was originally described by Hafezi et al 28 They reported no complications or progression of ectasia at 6 months in a series of 20 eyes with 4320 mm initial corneal thickness after epithelial removal. Similar encouraging 1 year results for CXL using hypotonic riboflavin in thinner corneas were reported by Raiskup et al 29 in a prospective series of 32 eyes.…”
Section: Keratocyte and Endothelial Cell Toxicitymentioning
confidence: 97%
“…In the event that pachymetry readings dropped below 400 mm, a hypotonic riboflavin solution (Vitamin B2 Streuli, Streuli Pharma, Uznach, Switzerland) was used to increase stromal thickness. 10 Penetration of riboflavin into the aqueous humor was verified by slit lamp examination (blue light) before irradiating the eye for 30 min with ultraviolet-A light (370 nm) with an irradiance of 3 mW/cm 2 (UV-X System; Peschke Meditrade GmbH, Huenenberg, Switzerland). During irradiation, 0.1% riboflavin drops were instilled every 5 min and further anesthetic drops if needed by the patient.…”
Section: Surgical Techniquementioning
confidence: 99%